Faktor Internal-Eksternal Ibu Post Partum dalam Inisiasi Menyusui Dini di Wilayah Kerja Puskemas Seberang Padang Kota Padang: Studi Fenomenologi - Agus Sri Banowo (Jurnal Keperawatan Muhammadiyah, 2021)
Objective: This study aimed to determine the experience of The mother who serve Early Initiation of Breastfeeding in working area Seberang Padang Community Health Center, Padang City.Methods:The research used qualitative methods with descriptive design phenomenology with seven samples as the informant. Data collection uses two methods by Focus Group Discussion and in-depth interviews. The data colectived trough Focus Group Discussion to identify some informants who have a broad and communicative insight, then informant taken as the key informant for in-depth interviews. Data saturation obtained on the fourth and fifth informants, so this research is sufficient with five informants. Results:By analyzed data, identified several themes, such as Mothers has a good understanding about early initiation of breastfeeding, there is mother’s positive response when initiating early breastfeeding, mother’s decision to initiate early breastfeeding based on well knowledge, there is a negative perception of the first breast milk that has entrenched among the elderly, mother gets support from the nearest person to implement of Early Breastfeeding Initiation, as well as hope that early initiation of breastfeeding continues to run and the presence of more information about the early initiation of breastfeedingConclusion:Based on study results, we expected health workers to be more aggressively provide information to pregnant women and their families for Early Initiation of Breastfeeding widely known in any society, so that Early Initiation of Breastfeeding not considered an unusual act.